(3odeM GdoedMs - (3SYO Hf Ydj Hf GdbGSe GdCfUGQj GdNRQLj GdMXjQj, CHh GdeYGdj (B( (3nOnqdGd GdocoJH (B)(3,J (B568 (3g` s ((3YjSi Hf jhSa GdCfUGQj s)
(3ChdgG (B:s
(3hHYO, HCYPH GdcdGe hbO LeYJ cJGHkG JaQb CHhGHkG s
(3BNQgG (B:s
(3hGdeYhd Ydi eSGeMI GdfGbO GdcGTa dbOQg, heUGdMI GdMGSO GdcGSa dHOQg s
(3ocJHJ ddCejQ TGOjs
(3hGdfSNI HgG VHWs
(3fSNI KGfjIs
(3JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa jSjQ aj HYV GdCdaGXs
(3hHgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
Keywords: (3GdCOHs